2018
DOI: 10.1186/s13104-018-3170-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of pro-apoptotic effects and mitochondrial potential on B16F10 cells by DODAC/PHO-S liposomes

Abstract: ObjectiveWe aimed to evaluate the potential of DODAC/PHO-S liposomes on the modulation of the expression of pro-apoptotic proteins, loss of lysosomal integrity and the mitochondrial electrical potential, compared with phosphoethanolamine.ResultsThe results of this study demonstrate that DODAC/PHO-S liposomes have exhibited broad cytotoxic potential in B16F10 murine melanoma cells, with significantly greater proportions than treatment with PHO-S. The treatment with the DODAC/PHO-S 2.0 mM liposomal formulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
10
0
3
Order By: Relevance
“…Another study reported the encapsulation of phosphoethanolamine (PHO-S, Figure 13), a phosphoric ester, into cationic liposomes (Table 3, C13). This nanoformulation demonstrated high cytotoxic activity towards B16F10 melanoma cells, compared with free compound, through induction of G 2 /M-phase cell cycle arrest (Table 4, F11) [185], as well as modulation of the expression of pro-apoptotic proteins (Table 4, F12) [186].…”
Section: Nanotechnology and Cancer Treatment—tackling Melanomamentioning
confidence: 99%
“…Another study reported the encapsulation of phosphoethanolamine (PHO-S, Figure 13), a phosphoric ester, into cationic liposomes (Table 3, C13). This nanoformulation demonstrated high cytotoxic activity towards B16F10 melanoma cells, compared with free compound, through induction of G 2 /M-phase cell cycle arrest (Table 4, F11) [185], as well as modulation of the expression of pro-apoptotic proteins (Table 4, F12) [186].…”
Section: Nanotechnology and Cancer Treatment—tackling Melanomamentioning
confidence: 99%
“…The analysis of protein expression were performed as previously published [ 15 , 16 ]. In brief, the Hepa1c1c7 cells (1 × 10 5 cells/well, the cell density reached 80 to 90% confluence), were treated with PHO-S (0.3–2.0 mM), DODAC/PHO-S 1:1 (0.3–2.0 mM), and empty DODAC (0.3–2.0 mM), for 12 h, were washed with PBS and resuspended in FACS buffer with 2.5% paraformaldehyde for 1 h. After washing, cells were again resuspended in a primary antibody specific for the proteins anti-CD44, anti-CD90, anti-p53, anti-p21, anti-p27, anti-Bax, anti-Bcl-2, anti-caspase-3, anti-caspase-8 (Abcam, Cambridge, MA, United States); anti- cytochrome c, anti-DR4 (Santa (Cruz Biotechnology Inc., Santa Cruz, EUA) and anti-cyclin D1 (Cell Signaling Technology, Danvers, MA), at a concentration of 1 μg/ml at 4 °C, for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…The Hepa1c1c7 cells were plated on sterile glass slides in 24-well plates, at concentration of 10 5 . After 24 h, the cells were treated with PHO-S and DODAC/PHO-S (1:1) at 0.3 and 2.0 mM, for 6 h. Then, the incubation with rhodamine-123 and analyses were perfomed as previously published [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this aim, our group has expressed interest in exploring the activity of 2-aminoethyl dihydrogen phosphate (2-AEH2P) as a therapeutic adjuvant through in vitro and in vivo studies involving various types of cancer. Indeed, 2-AEH2P has modulated proliferative and apoptotic effects in human breast cancer cells with estrogen, progesterone, and glucocorticoid receptors (MCF-7) [24], in triple-negative breast cancer cells (MDA-MB-231) [25], murine melanoma (B16-F10) [26], K-562 and K-562 MDR(+) myeloid leukemia [27], and murine hepatoma (Hepa-1c1c7) [28], indicating significant data in these cell lines regarding the reduction of mitochondrial membrane potential and the expression of markers involved in cell death, angiogenesis, and proliferation. In turn, paclitaxel (PTX) is a widely used chemotherapy agent in the treatment of advanced metastatic breast cancer [29].…”
Section: Introductionmentioning
confidence: 99%